A Decade of Inequality between the Rich and the Poor in Utilizing Antenatal Care Services in Nepal (2006-2016) - Shrestha, Bidhya (International Research Journal of MMC, 2022)
The utilization of antenatal care service (ANC) in Nepal is in an increasing trend; however, the utilization pattern differs from socioeconomic factors. Issues are the same but the utilizing pattern of ANC is not the same among women of the same age groups. The Sustainable Development Goals (SDGs) has also focused on inclusive and equitable health services, and promised to no one left behind. In this regard, this study aims to explore a decade of inequality between the rich and the poor in utilizing the ANC in Nepal using the three consecutive Nepal Demographic Health Surveys i.e., 2006, 2011 and 2016. Results suggest that women's household economies divide the pattern of ANC utilization. Despite the tremendous progress in health technologies, the utilization of ANC coverage gap between the rich and poor are still prevalent. The evidence from a decade inequality between the rich and the poor suggests that ANC services should be improved in Nepal, especially among the poor women who are concerned about their own health as well as the newborn health.